Kids on youtube : technical identities and digital literacies - Lange, Patricia G. (Walnut Creek,CA : Left Coast Press, 2014)
"The mall is so old school-these days kids are hanging out on YouTube, and depending on whom you ask, they're either forging the digital frontier or frittering away their childhoods in anti-intellectual solipsism. Kids on YouTube cuts through the hype, going behind the scenes to understand kids' everyday engagement with new media. Debunking the stereotype of the self-taught computer whiz, new media scholar and filmmaker Patricia G. Lange describes the collaborative social networks kids use to negotiate identity and develop digital literacy on the 'Tube. Her long-term ethnographic studies also cover peer-based and family-driven video-making dynamics, girl geeks, civic engagement, and representational ethics. This book makes key contributions to new media studies, communication, science and technology studies, digital anthropology, and informal education"--
Ways with video -- Video-mediated friendships: specialization and relational expertise -- Girls geeking out on YouTube -- Mediated civic engagement -- Video-mediated lifestyles -- Representational ideologies -- On being self-taught -- Studying YouTube: an ethnographic approach.
Includes bibliographical references (pages 237-263) and index.
Machine generated contents note: Chapter 1: Introduction: Ways With Video Chapter 2: Video-Mediated Friendships: Specialization and Relational Expertise Chapter 3: Girls Geeking Out on YouTube Chapter 4: Mediated Civic Engagement Chapter 5: Video-Mediated Lifestyles Chapter 6: Representational Ideologies Chapter 7: On Being Self-Taught Chapter 8: Conclusion Appendix: Studying YouTube: An Ethnographic Approach References Index About the Author.
Keywords: Internet and children; Internet -- Social aspects